THE MATHEMATICAL MODEL OF FRICTIONAL-PLASTIC ABSORBING MACHINE - Myamlin, S. V.; Naumenko, M. Ye.; Nikitchenko, O. O. (Science and Transport Progress, 2008)
The algorithm of construction of mathematical model for operation of a friction shock absorber is considered.